2013
DOI: 10.1089/thy.2012.0329
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Clinicopathological Characteristics and Outcomes of Thyroid Cancer in Korea over the Past Four Decades

Abstract: The incidence of thyroid cancer has rapidly increased, with a decrease in tumors of large size, LN involvement, and ETE, although the decreasing rates of LN involvement and ETE were not as prominent as decreasing rates of large size tumors. The mortality and recurrence rates have also decreased. Future long-term follow-up of patients diagnosed in the most recent decade is needed to confirm the prognostic characteristics of Korean PTC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 48 publications
10
129
0
2
Order By: Relevance
“…As described in our previous study (4), the use of total thyroidectomy has gradually increased from 22.5% (pre-1990) to 49.1% (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) and, finally, 94.3% (post-1999) ( Table 1). The use of prophylactic central or anterior neck LN dissection began in 2003 and has been increasingly performed in most patients with PTC R1 cm in our hospital starting in 2007.…”
Section: Treatment and Follow-upsupporting
confidence: 58%
See 4 more Smart Citations
“…As described in our previous study (4), the use of total thyroidectomy has gradually increased from 22.5% (pre-1990) to 49.1% (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999) and, finally, 94.3% (post-1999) ( Table 1). The use of prophylactic central or anterior neck LN dissection began in 2003 and has been increasingly performed in most patients with PTC R1 cm in our hospital starting in 2007.…”
Section: Treatment and Follow-upsupporting
confidence: 58%
“…As the proportion of patients diagnosed through screening tests has increased, epidemiologic studies have also indicated an increase in the proportion of smaller tumors (!1 cm diameter), a decrease in LN involvement, a decrease in ETE, and improved prognostic outcomes (4,9). These changes might also be related with temporal changes in the previously well-known prognostic factors.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations